Thermal Load Influence during the Formation of Al-Al Contacts on the Electrical Parameters of the Integrated Circuits with Aluminum-Polysilicon Contacts - V. A. Pilipenko; V. A. Solodukha; N. S. Kovalchuk; J. A. Solovjov; D. V. Shestovski; D. V. Zhyhulin (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2022)
This work is devoted to establishing the effect of using rapid thermal processing (RTP) method (450 °C, 7 s) to form an ohmic contact between two layers of aluminum metallization on the electrical parameters and reliability of integrated circuits. The resistance values of contact chains aluminum-silicon, aluminum-polysilicon, polysilicon-silicon n+, aluminum-silicon n+, current-voltage characteristics of the tested bipolar transistors, as well as the results of the reliability analyses by conducting thermal field tests were chosen as the analyzed parameters of this microcircuit. Comparison of these parameters was carried out with respect to the microcircuits manufactured using standard RTP method (450 °C, 20 min) to form this contact. An analysis of the results of the resistance value of various contact chains showed that, regardless of the type of thermal treatment, all contact chains, with the exception of the aluminum-polysilicon contact chain, have almost the same resistance. By analyzing the elemental composition of the cleavage in the area of this contact by scanning electron microscopy, it was found that during rapid heat treatment, the depth of penetration of aluminum into polysilicon is 2 times less than during its standard formation due to a 2-fold reduction in the time of exposure to high temperature compared to the standard process. This leads to a lower concentration of the aluminum in the silicon and as a result to a higher contact resistance between the aluminum and polysilicon. An analysis of the currentvoltage characteristics showed that they are all identical, except for the course of the direct branch of the base current value from the emitter-base voltage. The deviation of the linear nature of this dependence in the region of their low voltage values (£ 200 mV) in the case of the formation of ohmic Al-Si and Al-Al contacts with the use of long-term heat treatments is due to the predominance of the generation-recombination current in this region associated with an increased density of traps in the depleted region and on the surface of the semiconductor. The ideal behavior of the base current versus the emitter-based voltage is maintained by applying rapid RTP method to form an Al-Al contact by eliminating traps both in the depletion layer and on the surface of the semiconductor. The tests carried out on the reliability of these products showed that it does not depend on the type of formation of ohmic contacts between the metallization layers.